Tiktok's Edutok: A Learning Tool for Grammar - Karen Mosende; Seth Danielle Ada; Angelica Redita (Prodi Sastra Inggris, Universitas Muhammadiyah Semarang, 2024)
This study aims to investigate the impact of educational TikTok videos on Grade 11 students’ learning of grammar via a pretest-posttest experiment. While previous studies have been able to demonstrate the effectiveness of TikTok in increasing student engagement, there still exists little evidence indicating the effectiveness of TikTok on actual learner performance through formal graded assessments. This study is one of the first attempts to investigate the effects of TikTok as a learning tool on learner performance through a controlled experiment. Sixty-seven (67) Grade 11 students from St. Dominic College of Asia who are low-performing in English represent the population. A one-group pretest posttest experiment was used as the data collection method. In the experiment, the participants’ English subject teacher administered (via Google Meet) an online grammar test (via Google Forms) before and after exposing them to a selection of ten (10) educational TikTok videos by Filipino educational content creators. Moreover, qualitative and quantitative analysis (paired samples t-test) were used as data analysis methods. Overall, the evidence from this study indicates positive feedback as most of the students preferred this new method as compared to the traditional mind-map due to its novelty as well as the interesting features. Apart from that, the use of TikTok by familiar social media influencers demonstrates its effectiveness as a learning tool since the more students feel connected to someone, the more that they trust the person and adhere to the information given, so it signifies a better learning experience. Despite the small sample size and its exploratory nature, this study offers some insight into the possibility of integrating social media into language education. However, further work is needed to assess the application of this method with other language components such as reading, writing, pronunciation, and vocabulary enrichment.